Organic Farming in Bogor, West Java, Indonesia: Measuring How far Its Sustainability - Adil, Adityawarman; Syarif, Rizal; Najib, Mukhammad; Widiatmaka (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2023)
Sustainable organic farming management combines ecological/environmental, economic, and social interests in its implementation. This study aims to determine the sustainability status of organic agriculture in Bogor, West Java Province, on the ecological, economic, and social dimensions. The analytical method used is Multi-Dimensional Scaling (MDS) through the Rap-Organic Farm (Rapid Appraisal for Organic Farm) ordinance technique. The results showed that the sustainability status of organic farming in Bogor was categorized as Fairly Sustainable (58.57) on the ecological dimension. Still, the economic and social dimensions were moderately sustainable (52.09 and 53.70, respectively). Leverage attributes that very sensitive influenced the sustainability of organic agriculture are the availability of fertile land, the presence of organic product seeds, community consumption level for organic products, the market potential for organic products, average additional community income from organic product cultivation, and involvement of community institutions in organic farming development. The six attributes of levers must be prioritized for managers through the preparation and implementation of appropriate policies so that the sustainability of organic farming in Bogor, West Java, can be maintained.